2021
DOI: 10.1017/s146039692100042x
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of portal dosimetry pre-treatment quality assurance of intracranial SRS/SRT VMAT treatment plans

Abstract: Background: The complexity associated with the treatment planning and delivery of stereotactic radiosurgery (SRS) or stereotactic radiotherapy (SRT) volumetric modulated arc therapy (VMAT) plans which employs continuous dynamic modulation of dose rate, field aperture and gantry speed necessitates diligent pre-treatment patient-specific quality assurance (QA). Numerous techniques for pre-treatment VMAT treatment plans QA are currently available with the aid of several different devices including the electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Popular measurement-based methods for PSQA of lung SBRT plans include film, [7][8][9] multi-dimensional diode arrays, [10][11][12] high-resolution diode arrays, 10,13,14 and electronic portal imaging device (EPID) based QA. 12,[15][16][17][18] Due to the use of small field segments and steep dose gradients that are associated with lung SBRT plans, previous studies have demonstrated the need to use high resolution measurement methods to be able to detect potential errors through the use of stricter gamma criteria. 10,12,17 However, even with high resolution measurement devices, the sensitivity of measurement based QA to detect errors has been shown to be limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Popular measurement-based methods for PSQA of lung SBRT plans include film, [7][8][9] multi-dimensional diode arrays, [10][11][12] high-resolution diode arrays, 10,13,14 and electronic portal imaging device (EPID) based QA. 12,[15][16][17][18] Due to the use of small field segments and steep dose gradients that are associated with lung SBRT plans, previous studies have demonstrated the need to use high resolution measurement methods to be able to detect potential errors through the use of stricter gamma criteria. 10,12,17 However, even with high resolution measurement devices, the sensitivity of measurement based QA to detect errors has been shown to be limited.…”
Section: Introductionmentioning
confidence: 99%
“…12,[15][16][17][18] Due to the use of small field segments and steep dose gradients that are associated with lung SBRT plans, previous studies have demonstrated the need to use high resolution measurement methods to be able to detect potential errors through the use of stricter gamma criteria. 10,12,17 However, even with high resolution measurement devices, the sensitivity of measurement based QA to detect errors has been shown to be limited. [19][20][21][22] Similar to lung SBRT, single isocentre multi-lesion SRS plans frequently make use of small field segments and high dose gradients.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 One challenge in treating patients with large numbers of mets in a single isocenter setup is performing robust plan quality assurance (QA) that will measure the dose delivered to all targets to the high resolution necessary for cranial SRS. Portal dosimetry 6 is able to verify plan delivery for intensity-modulated radiation therapy (IMRT), VMAT, and SRS plans 7,8 for both individual and composite fields. However, due to the high Z material in the phosphor layer and the relatively shallow depth of measurement, the portal imager is known to overrespond to low-energy radiation.…”
Section: Introductionmentioning
confidence: 99%